2014
DOI: 10.1039/c4ee01873g
|View full text |Cite
|
Sign up to set email alerts
|

Dual-graphite cells based on the reversible intercalation of bis(trifluoromethanesulfonyl)imide anions from an ionic liquid electrolyte

Abstract: We present highly promising results for the use of graphite as both electrodes in a “dual-carbon” cell. An ionic liquid-based electrolyte mixture allows stable and highly reversible ion intercalation/de-intercalation into/from the electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
332
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 354 publications
(352 citation statements)
references
References 33 publications
13
332
0
7
Order By: Relevance
“…LICs, are a special form of "hybrid capacitors," i.e., a combination of a supercapacitor electrode and a battery electrode in one device, i.e., both storage mechanisms (Li ion insertion/extraction and adsorption/desorption) occur simultaneously during charge/discharge ( Figure 15b). As like in dual ion batteries, which are based on a similar working mechanism [150][151][152][153], not only the electrode capacities but also the number of anions and cations in the electrolyte, thus the amount of electrolyte is decisive for the available energy density. Amatucci et al [154,155] reported in 2001 the use of nanostructured lithium titanate (LTO) as negative electrode in combination with an activated carbon positive electrode.…”
Section: Pre-lithiation In Lithium-ion Capacitorsmentioning
confidence: 99%
“…LICs, are a special form of "hybrid capacitors," i.e., a combination of a supercapacitor electrode and a battery electrode in one device, i.e., both storage mechanisms (Li ion insertion/extraction and adsorption/desorption) occur simultaneously during charge/discharge ( Figure 15b). As like in dual ion batteries, which are based on a similar working mechanism [150][151][152][153], not only the electrode capacities but also the number of anions and cations in the electrolyte, thus the amount of electrolyte is decisive for the available energy density. Amatucci et al [154,155] reported in 2001 the use of nanostructured lithium titanate (LTO) as negative electrode in combination with an activated carbon positive electrode.…”
Section: Pre-lithiation In Lithium-ion Capacitorsmentioning
confidence: 99%
“…One academic expert raised the possibility of moving to a cell with both electrodes made of graphite based on the hybridisation of LiB and supercapacitor technology, leading to cycle lives of hundreds of thousands of cycles now more associated with supercapacitors, but with higher energy densities more associated with batteries. Such cells are currently under commercialisation (Power Japan Plus, 2014), but do not appear to have been reported as having exceptionally high cycle life (Read et al, 2014;Rothermel et al, 2014).…”
Section: Drivers Of Cost and Cycle Life Improvementsmentioning
confidence: 99%
“…6b). The coulombic efficiencies are above 100% in the subsequent cycles possibly due to the dual-ion battery effect of Cr 2 O 5 [36][37][38]. In the first two cycles, the charge curves correspond to the activation of Li 2 MnO 3 phase and the initial charge-discharge capacity are relatively lower than that in the half-cell just because of the twice activation (Fig.…”
Section: $57and/(6mentioning
confidence: 95%